Evaluation of teachers' knowledge about dental injuries in primary schoolchildren in the city of Isfahan - Dana Tahririan; Zahra Entezam; Saba Safarzadeh (Wolters Kluwer Medknow Publications, 2022)
Background: Dental trauma is a common problem in children, which mostly occurs at school. Traumatic dental injuries often cause unpleasant experiences for children, and immediate and appropriate measures are needed. Its prognosis depends on immediate posttraumatic measures, and schoolteachers can play a key role in the treatment of children. The current study aimed to investigate teachers' knowledge about dental injuries in primary school children in the city of Isfahan. Materials and Methods: Following a cross-sectional design, the current study was conducted on 248 elementary school teachers who were selected using the simple two-stage random cluster. Then the teachers' knowledge was measured based on a four-choice questionnaire consisted of two parts. According to this questionnaire, teachers were divided into five categories based on their knowledge score which was consist of strongly high knowledge, high knowledge, average knowledge, low awareness, and strongly low knowledge. Data were analyzed using the Spearman correlation coefficient and independent t-test. Statistical significance was considered when P < 0.05. Results: The total knowledge score of teachers was 45.9%. About 61% of the teachers had a history of exposure to dental injuries. Furthermore, 49.6% of them believed milk was the best environment to keep the avulsed teeth. There was no significant association between teachers' knowledge and education level, history of previous trauma, or participation in a training course, but there was a direct association between teachers' knowledge and their work experience (P < 0.05). Female teachers' knowledge score was significantly higher than their male counterparts (P < 0.001). Conclusion: Participants had a moderate level of knowledge about the management of dental traumas. Hence, it is suggested to develop educational programs to increase teachers' awareness about this issue.